In vivo efficacy and safety of systemically administered serinol nucleic acid-modified antisense oligonucleotides in mouse kidney - Toshiki Tsuboi; Keita Hattori; Takuji Ishimoto; Kentaro Imai; Tomohito Doke; Junichiro Hagita; Jumpei Ariyoshi; Kazuhiro Furuhashi; Noritoshi Kato; Yasuhiko Ito; Yukiko Kamiya; Hiroyuki Asanuma; et al. (Molecular Therapy: Nucleic Acids)
Nucleic acid medicine encompassing antisense oligonucleotides (ASOs) has garnered interest as a potential avenue for next-generation therapeutics. However, their therapeutic application has been constrained by challenges such as instability, off-target effects, delivery issues, and immunogenic responses. Furthermore, their practical utility in treating kidney diseases remains unrealized. Recently, we developed a serinol nucleic acid-modified ASO (SNA-ASO) that exhibits significant nuclease resistance. In this study, we evaluated the in vivo efficacy of SNA-ASOs in mouse kidney. We subcutaneously administered various types of phosphorothioate-modified gapmer ASOs with SNA or 2′-O-methoxyethyl (2′-MOE) modifications (MOE-ASO) targeting sodium glucose cotransporter 2 (SGLT2) in mice. The subcutaneous administration of SGLT2-SNA-ASO led to a dose-dependent reduction in renal SGLT2 expression and subsequent glucosuria. The inhibitory effects of SGLT2-SNA-ASO were more potent and prolonged than those of ASOs without SNA. Moreover, SGLT2-SNA-ASO did not cause severe liver damage, unlike SGLT2-MOE-ASO. The administration of Cy5-labeled-ASOs demonstrated an early increase in renal uptake, particularly in the renal proximal tubules, when modified with SNA. In conclusion, systemic administration of SGLT2-ASO modified with the artificial nucleic acid SNA effectively suppressed renal SGLT2 expression and induced urinary glucose excretion. These results suggest that SNA-modified ASOs show potential for application in developing nucleic acid therapeutics.